Fungsi Estetik dan Didaktik Sastra Lisan Bedandeng Kutai Kartanegara: The Aesthetic and Didactic Functions of the ‘Bedandeng’ Oral Literature of Kutai Kartanegara - Hafidzah, Luthfia Yaumil; Ulwatunnisa, Marwah (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2026)
The Bedandeng oral tradition is an intangible cultural heritage of the Kutai Kartanegara community, rich in local wisdom. However, this tradition currently faces the threat of extinction due to a lack of transmission to younger generations. This study aims to describe the aesthetic and didactic functions of Bedandeng oral literature. The aesthetic function focuses on the elements of rhyme and metaphor, while the didactic function encompasses moral, social, and reflective values. This study employs a descriptive qualitative approach. Data in the form of Bedandeng oral texts were collected through in-depth interviews with singers and cultural figures using purposive sampling, as well as documentary analysis. Data analysis was conducted using the interactive model which includes data condensation, data presentation, drawing conclusions, and verification. The results indicate that the aesthetic function of Bedandeng is realized through consistent end-rhyme patterns (vowels /a/, /-an/, and /i/) and the use of metaphors that deepen emotional meaning. The didactic function encompasses educational values (religious, moral, social, and work ethic) as well as reflective values (introspection and spirituality). The linguistic beauty of Bedandeng has been shown to reinforce the delivery of moral messages, making it an effective medium for non-formal education. This study highlights the importance of integrating Bedandeng into the Merdeka Curriculum as a teaching resource rooted in local wisdom to support the preservation of cultural identity amid the tide of modernization.